1994
DOI: 10.1038/ki.1994.250
|View full text |Cite
|
Sign up to set email alerts
|

TNF production by the medullary thick ascending limb of Henle's loop

Abstract: Medullary thick ascending limb of Henle's loop (mTALH) tubules, isolated from kidneys of male Sprague-Dawley rats, expressed the gene for tumor necrosis factor (TNF) and released this cytokine when challenged with lipopolysaccharide (LPS). The TNF produced was biologically active, as determined by cytotoxic activity present in supernatants from LPS-stimulated mTALH, using the TNF-sensitive murine fibrosarcoma cell line, WEHI 164. The amount of TNF produced, approximately 75 nM, has previously been shown to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…TNF is produced by the mTAL in response to a variety of stimuli including lipopolysaccharide, angiotensin II, and calcium receptor activation (12,18,41,59). This cytokine acts via an autocrine mechanism to inhibit sodium transport in mTAL cells and is an endogenous inhibitor of NKCC2A mRNA accumulation, total NKCC2 expression, and NKCC2 activity (2,12,22).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNF is produced by the mTAL in response to a variety of stimuli including lipopolysaccharide, angiotensin II, and calcium receptor activation (12,18,41,59). This cytokine acts via an autocrine mechanism to inhibit sodium transport in mTAL cells and is an endogenous inhibitor of NKCC2A mRNA accumulation, total NKCC2 expression, and NKCC2 activity (2,12,22).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent studies have shown that TNF exhibits natriuretic effects, exerts a tonic inhibitory effect on the Na ϩ -K ϩ -2Cl Ϫ cotransporter (NKCC2), and inhibits endothelial nitric oxide synthase expression in the TAL (2,50,53,54). The mTAL produces TNF in response to several stimuli; however, knowledge regarding the pathways that contribute to TNF production by the kidney is limited (1,12,18,22,41,59). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that the TAL produces TNF in response to bacterial LPS, ANG II, and elevated extracellular calcium (15,21,28). Incubation of the TAL with TNF in vitro inhibited ouabain-sensitive Rb ϩ uptake (10), suggesting that TNF may inhibit transcellular sodium transport in the TAL.…”
mentioning
confidence: 99%
“…Although blood mononuclear cells represent the main source of TNF-␣, it is also reported to be produced in other cell types, including mesangial and proximal tubule cells of kidneys (2,38). Remarkably, TNF-␣ is also produced in the medullar thick ascending limb of Henle's loop (mTALH) under baseline conditions (20). Therefore it would not be unlikely if TNF-␣ could play an important role in the regulation of renal functions and in the control of renin production in JG cells in particular.…”
mentioning
confidence: 99%